2021
DOI: 10.3390/polym13152433
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Metal Organic Framework for Enhanced Mechanical, Flame Retardant and Ultraviolet-Blue Light Shielding Properties of Transparent Cellulose-Based Bioplastics

Abstract: From the perspective of sustainable development and practical applications, there has been a great need for the design of multifunctional transparent cellulose-based composite films. We herein propose a novel concept of improving the mechanical, fire-resistant and ultraviolet (UV)-blue light shielding properties of cellulose-based composite bioplastic films though in situ embedding nano-metal organic framework (MIL-125(Ti)-NH2) into regenerated cellulose gel. Regenerated cellulose hydrogel (CH) with a porous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It was observed that the mechanical performance, including tensile strength and elongation at break of the film, improved by 6.5 ~ 25.9%, and a slight increment in contact angle from 60.6° and 60.9° was also recorded. Hence, it has been concluded that the incorporation of nano-metal–organic frameworks in cellulose film can be used for the development of multifunctional film, which has application in the packaging of food (Sun et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the mechanical performance, including tensile strength and elongation at break of the film, improved by 6.5 ~ 25.9%, and a slight increment in contact angle from 60.6° and 60.9° was also recorded. Hence, it has been concluded that the incorporation of nano-metal–organic frameworks in cellulose film can be used for the development of multifunctional film, which has application in the packaging of food (Sun et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, due to their small size, controlled porosity, large surface area, and meanwhile, organic linking ligands or metal ions from the framework can create UV inhibitory and blocking properties. 31 Based on what was stated in the previous studies, the metal part in the MOF has a more prominent role for absorbing UV.…”
Section: Properties Of the Fabric Coated With Mofsmentioning
confidence: 88%
“…Previously, Rodion Kopitzky [6] studied cost effective bio-based plastic production by blending polylactic acid-polybutyrene with succinate-sugar beet pulp particles. In addition, cellulose-based composite material production was also reported by Sun et al [7]. They used cellulose powder, which was obtained from filter paper pulp, as raw material for cellulose hydrogel production.…”
Section: Introductionmentioning
confidence: 94%